Author Correction: Co-delivery of docetaxel and silibinin using pH-sensitive micelles improves therapy of metastatic breast cancer - Dong Xin-yue; Lang Tian-qun; Yin Qi; Zhang Peng-cheng; Li Ya-ping (Acta Pharmacologica Sinica, 2019)
The authors apologize that due to our neglect, in the initially published version of this article, wrong images were pasted for the C6 group when doing the pictures layout of Fig. 3. Because the related text in the paper stated that “The free C6 exhibits a dim green ﬂuorescence, while CM displays a stronger ﬂuorescence intensity” (page 1658, the left column, lines 8–17), and both the correct and the wrong images of the C6 group showed very weak ﬂuorescent intensity of coumarin-6, the arguments and conclu-sions of the original article are not affected. We apologize again for any inconvenience caused.